Development of Orodispersible Tablets of Candesartan Cilexetil-β-cyclodextrin Complex. (24th September 2013) - Sravya, Maddukuri; Deveswaran, Rajamanickam; Bharath, Srinivasan; Basavaraj, Basappa Veerbadraiah; Madhavan, Varadharajan
Abstract : The aim of this study was to investigate the use of inclusion complexation technique employing β -cyclodextrin in improving the dissolution profile of candesartan cilexetil, a BCS class-II drug, and to formulate the inclusion complex into orodispersible tablets. The inclusion complexes were formed by physical mixing, kneading, coevaporation, and lyophilisation methods. Inclusion complexes were characterized by FTIR, DSC, XRD, NMR, and mass spectral studies. Inclusion complexes prepared using kneading, and lyophilisation techniques in the molar ratio 1 : 5 with β -cyclodextrin were used for formulating orodispersible tablets by direct compression with different superdisintegrants like croscarmellose sodium, crospovidone, sodium starch glycolate, and low substituted hydroxypropyl cellulose in varying concentrations. The directly compressible powder was evaluated for precompression parameters, and the prepared orodispersible tablets were evaluated for postcompression parameters. Drug-excipient compatibility studies showed no interaction, and characterization proved the formation of inclusion complex. In vitro disintegration time was found to be within 3 minutes, and all the formulations showed complete drug release of 100% within 20 minutes. The optimized formulation was found to be stable after 6 months and showed no significant change in drug content. This work proved β -cyclodextrins to be effective solubilizing agent in improving the solubility of poorly water soluble drugs.